UPAYA MENINGKATKAN KETERAMPILAN TENDANGAN LURUS MELALUI MEDIA KARET ELASTIS DAN KURSI PADA EKSTRAKURIKULER PENCAK SILAT - Syarif , Maulana; Irwami, Astri Ayu; Susanti, Evi (Jurnal Porkes, 2024)
The problem of this research is that the quality of straight kicks at MAN 1 Bekasi has begun to decline. This study aims to examine the effect of elastic rubber media and chairs on straight kicking skills in extracurricular pencak silat MAN 1 Bekasi. This type of research is quantitative with the research method used, namely the experimental method. The experimental method can be interpreted as a research method used to find the effect of certain treatments on others under controlled conditions. The subjects in this study amounted to 15 extracurricular students of pencak silat MAN 1 Bekasi. Determining the sample using porposip sampling. The instruments used are pretest and posttest with 11 assessment indicators. So that the results showed that, elastic rubber media and chairs have a significant influence. there is a significant influence on elastic rubber media and chairs on the ability of straight kick skills of MAN 1 Bekasi martial arts extracurricular participants “. With a t value of 11.690 > t table 2.14479 and a significance value showing 0.001 < 0.05. The pretest data has an average value of 3.0933 and the posttest value has an average of 4.5460. Based on the analysis of research data and hypothesis testing, it can be concluded that there is a significant effect on elastic rubber media and chairs on the ability of straight kick skills for extracurricular pencak silat participants of MAN 1 Bekasi.